Rate of clearance of virulent Treponema pallidum (Nichols) from the blood stream of normal, Mycobacterium bovis BCG-treated, and immune syphilitic rabbits. - Graves, S (1980)
The rate of clearance of virulent Treponema pallidum (Nichols) from the blood stream of normal rabbits and rabbits previously treated with Mycobacterium bovis BCG was similar, there being treponemes still circulating 8 h after intravenous inoculation. In contrast, immune syphilitic rabbits cleared the virulent treponemes within 1 to 2 hours. Rabbits with passive humoral immunity to T. pallidum (after the transfer of 70 ml of immune serum) showed a similar clearance rate to that of the immune rabbits. Rabbits previously treated with BCG and with passive humoral immunity did not show a synergistic enhanced clearance rate, it being similar to that of immune rabbits.